Spline Function Interpolation Solving a Birkhoff Interpolation Problem for (0,1,5) data - Mishra, Rama Nand; Mishra, Akhilesh Kumar; SINGH, KULBHUSHAN (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2020)
Abstract: The following research work deals with a special type of Birkhoff interpolation problem in which we have 3 set of data prescribed in the unit interval I = [0, 1]. Data values are the function value, first derivatives and fifth derivatives prescribed at nodes of the unit interval. We obtained a unique spline interpolating the given data along with the convergence problem.